(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objectives The study's goal is to look into the effect of COVID-19 vaccines on adolescent female menstrual cycles. Methods From October 2021 to May 2022, a cross-sectional online self-administered survey was used for the study. Adolescent females above the menarche who had received the vaccine, were single, and without a previous history of primary ovarian insufficiency were the target population (language secondary school and first year student at faculty of physical therapy Kafrelsheikh university). Regional distribution of the survey was done through social media. Results a total of (270) female with mean age ranged from 16 to 18 years, with a mean of (16.98± 1.796). Overall, 66.6% of female didn't feel any changes in the period after vaccination, (10.7%) had Menstrual Cramps, (9.6%) irregular menstruation, (5.9%) increase the duration of the menstruation, (7.8%) Increased amount/abundance of bleeding, (4%) Increased period frequency and (5.19%) Worsening of premenstrual symptoms, (1.4%) intermenstrual bleeding, (37%) post menstrual bleeding. there was a significant relationship between duration of menstrual cycle in days and covid -19 vaccination p = 0.014, symptoms appearance in relation to dose p = .001, severity of vaccine side effect p= .023. Conclusion The study described a bearable link between the COVID-19 vaccine and the menstrual irregularities that have negatively impacted the women's quality of life.